Organosulphur, organoselenium and organotellurium compounds for the development of heterogeneous and nanocatalytic systems for Suzuki coupling. Issue 45 (11th November 2022) - Arora, Aayushi; Oswal, Preeti; Sharma, Deepali; Purohit, Suraj; Tyagi, Anupma; Sharma, Pankaj; Kumar, Arun
Abstract : Heterogeneous and nanocatalytic systems have been developed using organosulphur, organoselenium and organotellurium ligands and their complexes, and they have been used to catalyze Suzuki coupling reaction. Abstract : Suzuki–Miyaura cross-coupling (SMC) is an extremely useful reaction in organic syntheses. During the last two decades, many researchers across the world have employed organochalcogen compounds in various ways for the development of catalytic systems for this reaction. Chalcogen-ligated molecular complexes have been designed using such compounds as ligands, and applied as homogeneous catalytic systems. During the period 2013–2022, various heterogeneous and nano-catalytic systems have also been developed using organosulphur, organoselenium and organotellurium compounds. The main advantages associated with such systems are their easy synthesis and air- and moisture-insensitivity. This article aims to provide insights into the synthetic methodologies pertaining to the preparation of (i) these catalytically relevant and useful compounds and (ii) the heterogeneous and nano-catalytic systems designed using them. Another major focus of the article is to rationalize and critically analyse the effect of chalcogen donor on the size, composition, morphology and shape of the nanostructure. A critical analysis of the applications of all such catalytic systems in Suzuki–Miyaura coupling is presented in detail. Various factors ( e.g., temperature) which affect the catalytic performance are also rationalized. The effects of binding mode, ligand framework, chalcogen donor atom and metal are also covered, along with all other factors that influence the catalytic potential of the systems. Various other aspects such as green catalysis (in aqueous medium and in air), and use of non-conventional (ultrasonic radiation) energy sources are analysed. Applications of heterogeneous and nanocatalytic systems apart from Suzuki coupling are also highlighted, and challenges and future scope are elaborated.